1991
DOI: 10.1148/radiology.180.3.1871305
|View full text |Cite
|
Sign up to set email alerts
|

Lung parenchyma: magnetic susceptibility in MR imaging.

Abstract: Magnetic susceptibility effects in magnetic resonance (MR) imaging of normal lung parenchyma occur because of magnetic-field inhomogeneities induced by the microscopic heterogeneity of the lung. The effects on MR imaging of the lung are loss of signal from intravoxel phase dispersion (measured with T2') and a shift in the macroscopic resonant frequency from that of water toward that of air (delta v). These effects of MR imaging at 1.5 T were quantitated by measuring T2' decay and delta v at different locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
97
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 0 publications
0
97
0
3
Order By: Relevance
“…This decrease is due to the diffusion of the tissue protons in the field gradients created by the differences in the susceptibilities of the tissue and the capillary vascular space. Furthermore, susceptibility-based imaging of lung parenchyma using paired symmetricasymmetric spin echo has been reported (25,26). Since these studies rely on reporting changes in the T2 (or phase) of the protons of the surrounding tissues, their application is severely restricted in the lungs, where the proton concentration is low.…”
Section: Discussionmentioning
confidence: 99%
“…This decrease is due to the diffusion of the tissue protons in the field gradients created by the differences in the susceptibilities of the tissue and the capillary vascular space. Furthermore, susceptibility-based imaging of lung parenchyma using paired symmetricasymmetric spin echo has been reported (25,26). Since these studies rely on reporting changes in the T2 (or phase) of the protons of the surrounding tissues, their application is severely restricted in the lungs, where the proton concentration is low.…”
Section: Discussionmentioning
confidence: 99%
“…Since UTE-MRI of the lung was first demonstrated in the early 1990s on a 1.5 T system (28), most of the subsequent studies have been performed on animal MR systems at higher field strengths (14,15,18,22). Only recently, investigators performed UTE-MRI of the lung in animal models using clinical systems at 3.0 T (16,17).…”
Section: Te=01 Ms Te=21 Msmentioning
confidence: 99%
“…Recently, it was also shown that HASTE-MRI of the lungs is also feasible at 3 Tesla (T), and that a higher lesion contrast of nodules and infiltrates is observed at 3T when compared with 1.5T (13). For the lungs, however, susceptibility increases at higher field strength, which may degrade the image quality and thus reduce the effectiveness of lung MRI (14).…”
mentioning
confidence: 99%